PROTECTED, PROHIBITED, AND INVASIVE FISH DIVERSITY AND DISTRIBUTION IN RANAU LAKE OF WEST LAMPUNG DISTRICT - Sumino Sumino; Herman Mude; Santi Saluri Alam; Dini Dini (AQUASAINS, 2017)
The objectives of this research were to collect fish species in Ranau Lake of West Lampung District, analyze the fish community structure, determine the types of fish that are protected, prohibited, or invasive and mapping its distribution. Sampling was done on three locations: Station 1 (Suka Banjar), Station 2 (Kagungan), and Station 3 (Lombok). The data were analyzed by the structure of the community: diversity (H'), uniformity (E) and dominance index (C). The result of the identification indicate that there are 26 species of fish and total number of fish is 184. The results of the analysis of fish community structure in Ranau Lake have medium diversity, medium distribution and moderate community stability (H’=1.43), medium uniformity and volatile communities (E = 0.41),  low dominance and no dominant fish species (C = 0.32). From the 26 fish species in Ranau Lake, there are no protected and prohibited fish species, there are two types of fish categories as invasive alien species: nile tilapia (Oreochromis niloticus) and suckermouth catfish (Hypostomus plecostomus).